EMPLOYEE COMPETENCE DEVELOPMENT TO IMPROVE ORGANIZATIONAL PERFORMANCE IN THE DIGITAL ERA - Winarto, Sugeng; Engkur, Engkur (Jurnal Manajemen Dan Bisnis, 2026)
This research aims to analyze the direct influence of employe competency development on organizational performance, analyze the impact of the digital era on organizational performance, analyze the influence of employe competency development on the digital era, and examine the role of the digital era in mediating the relationship between employe competency development and organizational performance using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. Data were obtained thru the distribution of questionnaires to employes. Furthermore, this research emphasizes that the digital era can serve as a mediating variable that bridges the relationship between employe competency development and organizational performance. In other words, if digital transformation and the effective use of technology are utilized, the enhancement of employe competencies will be increasingly effective in improving organizational performance. Overall, this research is expected to provide a better understanding of the importance of integrating adaptation to the digital era and human resource development to enhance the sustainable performance of organizations.